2023
DOI: 10.1002/cpp.2932
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Self‐Reflection and Insight Scale for psychologists and the development and validation of the revised short version

S. E. Banner,
K. Rice,
N. Schutte
et al.

Abstract: Self‐reflection is broadly considered a core competency for psychologists; however, there is an absence of measures of self‐reflection, limiting the extent to which self‐reflection can be assessed in both research and practice contexts. Whilst the Self‐Reflection and Insight Scale (Grant et al., 2002) has been validated in a range of formats with different populations, it has not yet been validated with psychologists. Further, the psychometric properties of a short version of the scale (Silvia, 2021) have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(134 reference statements)
0
0
0
Order By: Relevance
“…Evidence for discriminant validity is obtained when one measure has only weak association with another measure that is theoretically not expected to overlap with the main measure of interest. For example, in an evaluation study of the Self-Reflection and Insight Scale (SRIS), Banner et al (2023) tested for discriminant validity by comparing the SRIS with the perceived knowledge subscale from the short form of the Career Futures Inventory ( Mcllveen, Burton & Beccaria, 2013 ). Banner et al (2023) reported no statistically significant correlation between these measures, concluding this represented some discriminant validity evidence for the SRIS.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for discriminant validity is obtained when one measure has only weak association with another measure that is theoretically not expected to overlap with the main measure of interest. For example, in an evaluation study of the Self-Reflection and Insight Scale (SRIS), Banner et al (2023) tested for discriminant validity by comparing the SRIS with the perceived knowledge subscale from the short form of the Career Futures Inventory ( Mcllveen, Burton & Beccaria, 2013 ). Banner et al (2023) reported no statistically significant correlation between these measures, concluding this represented some discriminant validity evidence for the SRIS.…”
Section: Discussionmentioning
confidence: 99%